Supervision in the Context of Lithuanian Social Work - Dirgėlienė, Irena; Kiaunytė, Asta (Acta Paedagogica Vilnensia, 2005)
The aim of this article is to show the possibilities of application of supervision in the context of Lithuanian social work. In the first part of the article the complexity of the social work is covered, actualizing the context of social work, the potential of interaction of the social worker ant the client. In the second part of the article the supervision is covered as a profession, contributing in the sphere of professional relations, and as a complex construct of the social work, where the social worker, the client and the social context interact in the multidimensional process of supervision. In the third part of the article the interferences and perks of supervision, which might be determined by Lithuanian cultural situation, are pointed up. The methodological principle of the article is predicted by postmodern philosophical direction, social construction, and the main ideals of system theory, paradigm of symbolic interaction, and the humanistic psychology. The analysis of implementation of the supervision to Lithuanian cultural context would influence the spread of this new profession; the material of this article might be significant for both the practicing supervisors and the recipient.